1977
DOI: 10.1159/000222013
|View full text |Cite
|
Sign up to set email alerts
|

Selected and Spontaneous Variants of <i>Serratia marcescens</i> with Combined Resistance against Chloramphenicol, Nalidixic Acid, and Trimethoprim

Abstract: Combined resistance against chloramphenicol (CHLOR), nalidixic acid (NA), and trimethoprim (TMP) was demonstrated in isolates and variants of a nosocomially significant, multiple-drug-resistant, nonconjugative strain of Serratia marcescens (bacteriocin type 18), either as a spontaneous event or after exposure of isolates and variants derived therefrom to increasing concentrations of CHLOR, NA, and TMP, respectively. This phenomenon was also noted among several selected mutants of two control strains of S. marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…are intrinsically resistant to TMP because of poor penetration through the cell wall (35,82). Acquired TMP resistance based on cell wall permeability has been reported in Klebsiella pneumoniae and Serratia marcescens (74,86). Alterations in outer membrane proteins have been found associated with resistance to multiple antimicrobial agents, including TMP, in Klebsiella, Enterobacter, and Serratia isolates (34).…”
Section: Mechanisms Of Tmp Resistancementioning
confidence: 99%
“…are intrinsically resistant to TMP because of poor penetration through the cell wall (35,82). Acquired TMP resistance based on cell wall permeability has been reported in Klebsiella pneumoniae and Serratia marcescens (74,86). Alterations in outer membrane proteins have been found associated with resistance to multiple antimicrobial agents, including TMP, in Klebsiella, Enterobacter, and Serratia isolates (34).…”
Section: Mechanisms Of Tmp Resistancementioning
confidence: 99%
“…It has been reported previously that the quinolone carboxylic acid derivatives are relatively less active when tested against bacterial isolates with an underlying resistance to certain beta-lactams and amikacin (2,(4)(5)(6). Many of our gentamicin-resistant strains of Acinetobacter sp., Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Serratia marcescens were also relatively or completely resistant to piperacillin and trimethoprim.…”
mentioning
confidence: 98%
“…San ders and Watanakunakorn [9] presump tively characterized the OMP of variants of a strain of S. marcescens that resisted amikacin, cefotaxime, and ciprofloxacin; it was noted that two OMP (38 and 42 kd) were altered in these variants. How ever, nonspecific S. marcescens resistance against chloramphenicol, DNA gyrase in hibitors (nalidixic acid) and trimethoprim previously had been shown to be due to yet another mechanism [3,12,13]. In partic ular, Gutman et al [3] found that S. mar cescens variants resistant against this group of unrelated antimicrobial drugs re vealed one OMP alteration; a 40-kd pep tide was reduced significantly.…”
Section: Discussionmentioning
confidence: 99%